Three distinct mechanisms underlying human γδ T cell-mediated cytotoxicity against malignant pleural mesothelioma - Umeyama, Yasuhiro; Taniguchi, Hirokazu; Gyotoku, Hiroshi; Senju, Hiroaki; Tomono, Hiromi; Takemoto, Shinnosuke; Yamaguchi, Hiroyuki; Tagod, Mohammed S. O.; Iwasaki, Masashi; Tanaka, Yoshimasa; Mukae, Hiroshi (Frontiers in Immunology, 2023)
Malignant pleural mesothelioma (MPM) is a rare and highly aggressive thoracic tumor with poor prognosis and limited therapeutic options. Although immune checkpoint inhibitors exhibit a promising effect in some patients with unresectable MPM in clinical trials, the majority of MPM patients show only modest response rates to the currently available treatments. It is thus imperative to develop novel and innovative therapeutic modalities for MPM, including immune effector cell-based therapies. Since we have recently developed a strategy to efficiently expand γδ T cells with potent anti-tumor activity from peripheral blood to purities up to 95–99% using tetrakis-pivaloyloxymethyl 2-(thiazole-2-ylamino) ethylidene-1,1-bisphosphonate (PTA) and interleukin-2, we set out to evaluate the therapeutic potential of γδ T cells against MPM in vitro. We successfully expanded γδ T cells from peripheral blood mononuclear cells of healthy donors and MPM patients. γδ T cells expressed natural killer receptors such as NKG2D and DNAM-1 and exhibited a moderate level of cytotoxicity to MPM cells in the absence of antigens. The inclusion of PTA, (E)-4-hydroxy-3-methylbut-2-enyl diphosphate (HMBPP) or zoledronic acid (ZOL) induced a TCR-dependent cytotoxicity in γδ T cells and secreted interferon-γ (IFN-γ). In addition, γδ T cells expressing CD16 exhibited a significant level of cytotoxicity against MPM cells in the presence of an anti-epidermal growth factor receptor (EGFR) mAb, at lower concentrations than in clinical settings, whereas a detectable level of IFN-γ was not produced. Taken together, γδ T cells showed cytotoxic activity against MPM in three distinct mechanisms through NK receptors, TCRs and CD16. Since major histocompatibility complex (MHC) molecules are not involved in the recognition, both autologous and allogeneic γδ T cells could be used for the development of γδ T cell-based adoptive immunotherapy for MPM.